The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acsomega.0c04915
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Polydopamine Particles as a Thermal Stability Modifier to Prepare Antifouling Melt Blend Composite Membranes

Abstract: This study reports a novel, multifunctional, and easily obtained modifier to support the rapid advancements in the field of filtration. Polydopamine (PDA) particles (PDAPs) have been reported as a filler for constructing polymer composites, but because of their poor thermal stability, the use of PDAPs in high-temperature blend melt systems to construct antifouling membranes was rare. In this paper, high-thermal-stability methoxy polyethylene glycol amine (mPEG-NH2)-functionalized PDA nanoparticles (mPDAPs) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…It has also been demonstrated that the PDA formed by the self-polymerization of dopamine on the surface of Fe 3 O 4 is thermally stable. For example, as a thermal stability modifier, PDA has been used to improve the perceived stability modification of carbon nanotubes and composite membranes. In addition, previous research on the thermal stability of Ag nanoparticles indicated that high temperatures would not affect the SERS-enhanced effect of Ag nanoparticles …”
Section: Resultsmentioning
confidence: 99%
“…It has also been demonstrated that the PDA formed by the self-polymerization of dopamine on the surface of Fe 3 O 4 is thermally stable. For example, as a thermal stability modifier, PDA has been used to improve the perceived stability modification of carbon nanotubes and composite membranes. In addition, previous research on the thermal stability of Ag nanoparticles indicated that high temperatures would not affect the SERS-enhanced effect of Ag nanoparticles …”
Section: Resultsmentioning
confidence: 99%
“…The formation of the rGO@R-Gel heterostructure originates from the fact that R-Gel and its oxidized R-Gel wrapped the rGO probably through P-P stacking or strong covalent bonds formed with the rGO surface. The Cu 2 O/rGO@R-Gel hybrid structure benefits from the continued growth of R-Gel and its further assembly by the induction of metallic copper ions or hydrogen bonding. The Cu 2 O/rGO@R-Gel heterostructure composed of Cu 2 O, rGO, and R-Gel, all three, has a large, smooth, and fluent exchange channel for water molecules (Figure a,b,g). This will play a crucial role in the practical antifouling application of Cu 2 O/rGO@R-Gel.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, PDA NPs have poor thermal stability. Thus, functionalizing PDA NPs by high-thermal-stability methoxy polyethylene glycol amine (mPEG-NH 2 ) showed an ability to construct antifouling melt blend composite membranes [ 125 ]. It can be said that PAD NPs with their multifunctional properties have shown promising prospects in enhancing different water purification membranes.…”
Section: Membrane’s Modification Based On Pda Nanoparticles Incorpora...mentioning
confidence: 99%